Temporal and visual source memory deficits among ecstasy/polydrug users. (21st January 2014) - Fisk, John E.; Gallagher, Denis T.; Hadjiefthyvoulou, Florentia; Montgomery, Catharine
<x xml:space="preserve">Abstract</x> Objectives We wished to investigate whether source memory judgements are adversely affected by recreational illicit drug use. Method Sixty‐two ecstasy/polydrug users and 75 non ecstasy users completed a source memory task, in which they tried to determine whether or not a word had been previously presented and if so, attempted to recall the format, location and temporal position in which the word had occurred. Results While not differing in terms of the number of hits and false positive responses, ecstasy/polydrug users adopted a more liberal decision criterion when judging if a word had been presented previously. With regard to source memory, users were less able to determine the format in which words had been presented (upper versus lower case). Female users did worse than female nonusers in determining which list (first or second) a word was from. Unexpectedly, the current frequency of cocaine use was negative associated with list and case source memory performance. Conclusions Given the role that source memory plays in everyday cognition, those who use cocaine more frequently might have more difficulty in everyday tasks such as recalling the sources of crucial information or making use of contextual information as an aid to learning. Copyright © 2014 John Wiley & Sons, Ltd.